La imagen “distorsionada”: sobre la relación entre perdón y deformidad en los textos Walter Benjamin - Esparza, Daniel R. (2020)
“Distorted Picture: on the Relationship Between Forgiveness and Deformity on Walter Benjamin’s Worka”. The hunchback we find here and there in Benjaminian texts, an image that Benjamin himself describes as the prototype of the distortion (“dem Urbilde der Entstellung”) is also the prototype of the subject in need of forgiveness. A critical reading of the places in which Benjamin refers to this “distorted image” offers the possibility of raising a theory of forgiveness (and, indirectly, of guilt and justice) that does not reduce forgiveness to a legal form, to some specific emotional dynamics, or to an exchange of moral conditions. Instead, I argue the Benjaminian hunchback endows our common understandings of forgiveness with a clear bodily dimension that is simply absent in most contemporary considerations of the matter.